Effects of Chemical Modifications on Mechanical Properties of Luffa cylindrica - Kocak, D.; Merdan, N.; Yuksek, M.; Sancak, E. (Asian Journal of Chemistry, 2012)
Among the natural fibres, Luffa cylindrica fibres are the ones that are widely available throughout the world. Luffa fibres are known to have lignocellulosic fibre characteristics. Depending on their use, there is work to make them more useful by means of chemical processes. For this aim, through two different processes, conventional and microwave, three different chemical processes were applied. The results obtained were examined with % weight loss values; mechanical properties, morphological characteristics (SEM) followed by FT-IR and X-ray diffraction properties. Three different processes chemical processes, carried out with formic acid and acetic acid were proved to be successful. The reason for the microwave processes to be successful is the strength achieved by sonication. In this study, formic acid and acetic acid processes were found to adequately modify the fibres surfaces.